Global incidence and prevalence of nonalcoholic fatty liver disease - Teng, Margaret LP; Ng, Cheng Han; Huang, Daniel Q.; Chan, Kai En; Tan, Darren JH; Lim, Wen Hui; Yang, Ju Dong; Tan, Eunice; Muthiah, Mark D. (Clinical and molecular hepatology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is a leading cause of liver disease worldwide. The estimated global incidence of NAFLD is 47 cases per 1,000 population and is higher among males than females. The estimated global prevalence of NAFLD among adults is 32% and is higher among males (40%) compared to females (26%). The global prevalence of NAFLD has increased over time, from 26% in studies from 2005 or earlier to 38% in studies from 2016 or beyond. The prevalence of NAFLD varies substantially by world region, contributed by differing rates of obesity, and genetic and socioeconomic factors. The prevalence of NAFLD exceeds 40% in the Americas and South-East Asia. The prevalence of NAFLD is projected to increase significantly in multiple world regions by 2030 if current trends are left unchecked. In this review, we discuss trends in the global incidence and prevalence of NAFLD and discuss future projections.